Analytical and statistical study of a lake system under various processes of eutrophication - Parinet, B.; Lhôte, A.; Legube, B.; Gbongue, M. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2000)
One of the problems water managers and researchers have had to deal with for a long time is that of identifying the symptoms of eutrophication, with all its multiple facets. The search for a simplified model of this complex process does not seem, so far, to have attained this objective. In order to identify and classify the various trophic states of waters (lakes or rivers), two main types of trophic indicators have been and are still being used, those belonging to the biocenosis (biological factors) and those belonging to the biotope (physical-chemical factors).- The aim of the biological approach to eutrophication is to measure its impact on the environment's biodiversity. Thus, several classification indices have been drawn up, for example: the Biotic Index, which is one of the oldest; the General Quality Biological Index, which has been improved to become the Normalised Global Biological Index (NGBI) method; and more recently the Trophic Diatom Index. Working with such indices requires quite complex analyses since it is necessary to identify the local fauna and flora. Furthermore, these indices only apply to rivers, not to lentic environments.- For the physical-chemical approach, the aim is to quantify the trophic state of an aquatic environment by measuring a number of physical-chemical parameters. This approach is easier to implement and the results provided are those currently used by water managers.It is obvious that the two approaches are linked, since the biodiversity of an aquatic environment is conditioned by the physical-chemical quality of its water. However, the study of the eutrophication process in surface waters faces two main difficulties, which are inherent in the very nature of the system and the phenomena under study:1. Since aquatic systems naturally differ one from the other, it is obviously difficult if not impossible to establish a reference state to determine the trophic level of a water with absolute accuracy.2. The second difficulty lies in the choice that must be made among the analytical parameters, to select those that are the most appropriate to describe the phenomenon. Although it is currently admitted that the nitrogen, phosphorus and phytoplankton parameters, among others, cannot be ignored, their intrinsic values are not sufficient to completely describe the process of eutrophication. Indeed, the values of most of these parameters are linked both to the causes and the effects of eutrophication, and as a consequence they cannot be interpreted unambiguously. The same restriction applies to correlations that are established between these parameters and the plant biomass. Because of the originality of the lake system with which we are dealing, the present study offers the opportunity to better understand the reasons for both these problems.The ten lakes we have studied (number 1 to 10) present the rare advantage of being supplied by the same streams, running across a restricted geographical zone that is geologically and climatically similar. However, the trophic characteristics of these waters have been altered by their passage through different agricultural and urban zones. Thus, lakes 1 to 4 are located in an area of low urban density and are colonised by phytoplankton, the density of which decreases from Lake 1 to Lake 4; macrophytes are not present in these lakes.Lake 5, located in the centre of the town, receives domestic waste water. This lake was, over a long period of time, entirely covered with water hyacinths (Eichhornia crassipes), very invasive floating macrophytes, and with lotuses (Nelumbo nucifera) and rooted macrophytes. During the study period, following the manual removal of the macrophytes in July 1995, the water was strongly colonised by algae, as can be seen from the high concentration of chlorophyll-a, close to 200 µg/l.Lake 6 presents a similar situation; it was almost entirely covered by Eichhornia crassipes until July 1997, and was then manually cleared. As the elimination of the water hyacinths profoundly modified the characteristics of this lake, we will show the two periods of time separately.Lake 7 receives the waste water from a densely populated area. After being cleared in July 1997 of a thick layer of various plants that had covered it for several years, the lake was invaded by water lettuce (Pistia stratiotes), a floating macrophyte, which has dominated the lake since December 1997.Finally lakes 9 and 10 are almost completely covered by lotuses (Nelubo nucifera), which are rooted macrophytes, along with a few Pistia stratiotes, while Lake 8 is periodically colonised by water lilies (Nymphea lotus) and algae.To follow changes in the water quality of the 10 lakes studied, 21 sampling stations were chosen, usually at the entrance and exit of each lake. The mean values for the physical-chemical parameters for any lake gave a reasonable representation of the lake water under study. Sample collection in the ten lakes lasted two hours (between 8 and 10 a.m.). The sample collection, and the analysis of the 19 physical-chemical parameters taken into account, was carried out between April 1996 and April 1998 (twice a month in the rainy season and once a month otherwise), which represented about 15 000 measurements. At each location, a litre of water was taken, 50 cm below the surface, with a polyethylene bottle fixed on a 5 m bamboo pole. Portions of 250 ml were then transferred into a brown glass bottle, for later analysis of chlorophyll. After the in-situ analyses, the bottles were kept in the dark in a cooler.Because of the unique sampling situation, it might have been anticipated that the comparison of the different trophic states on the basis of the physical-chemical variables would be possible, but this was not the case. On the contrary, this study tended to show that the physical-chemical characteristics of these waters are as much influenced by the feedback effect of eutrophication as by the external factors, so that the contribution of each of the variables to the various types of eutrophication cannot be clearly determined. This is particularly true in the case of parameters characteristic of nutrients or those reflecting the water response.Although it may appear trivial, this "feedback action" can naturally be generalised to all lake systems, in temperate or tropical climates, whatever the kind of biomass that colonises them. The trophic level of these waters must therefore be evaluated on the basis of new criteria, which will take into account all the relations that link the various parameters.